URBANIZATION AND DISINTEGRATION OF LOCAL COMMUNITIES: A LITERATURE REVIEW OF THE EROSION OF SOCIAL COHESION WITHIN URBAN SPACES: URBANISASI DAN DISINTEGRASI KOMUNITAS LOKAL: TINJAUAN LITERATUR ATAS EROSI KOHESI SOSIAL DALAM RUANG KOTA - Eko Budi Siswandoyo; Armando Dos Santos Lopes; Joao Ximenes; Oman Sukmana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Urbanization as part of the modernization process has changed the social structure and living space of people, especially in urban areas. This study aims to systematically review the literature related to the impact of urbanization on social cohesion in local communities and to analyze the dynamics of social disintegration that arise in urban spaces. The research uses a qualitative approach with a systematic literature review method, based on the perspective of critical sociology and social cohesion theory. Data is collected from scientific journal articles, academic books, research reports, and policy documents obtained through scientific databases such as Scopus, Google Scholar, and Web of Science. The analysis was carried out thematically and interpretively on the selected relevant literature published from 2017–2025. The results of the study show that urbanization triggers the erosion of communal solidarity, strengthens spatial segregation, and decreases the sense of belonging between city residents. Processes such as gentrification and social exclusion deepen inequality and marginalize traditional communities. This research confirms the importance of inclusive and participatory community-based urban planning to rebuild lost social cohesion. This study provides a conceptual basis for the development of socially just and sustainable spatial planning policies